2018
DOI: 10.1096/fj.201700800r
|View full text |Cite
|
Sign up to set email alerts
|

Double‐strand DNA breaks are mainly repaired by the homologous recombination pathway in early developing swine embryos

Abstract: DNA double-strand breaks (DSBs) are less frequent than single-strand breaks but have more harmful consequences on cell survival and physiology. Homologous recombination (HR) and nonhomologous end-joining (NHEJ) are the two main pathways that are responsible for DSB repair in eukaryotic cells, but their importance for the preservation of genome stability in totipotent blastomeres of early developing embryos has not been determined. In this study, we observed that the chemical inhibition of HR or both pathways, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 56 publications
1
24
0
Order By: Relevance
“…The fluorescence intensity for H3K4me1, H3K4me2, H3K4me3, H3K9me1, H3K9me2, and KDM5B was quantified on each nucleus and corrected to the background in the cytoplasm of each embryo using the SimplePCI imaging software (Compix, Sewickley, PA, United States). The same software was used to determine the number of DSBs by counting the number of H2AX139ph foci ≥0.3 µm 3 in each nucleus (Bohrer et al, 2018).…”
Section: Immunofluorescence and Cell Counting Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluorescence intensity for H3K4me1, H3K4me2, H3K4me3, H3K9me1, H3K9me2, and KDM5B was quantified on each nucleus and corrected to the background in the cytoplasm of each embryo using the SimplePCI imaging software (Compix, Sewickley, PA, United States). The same software was used to determine the number of DSBs by counting the number of H2AX139ph foci ≥0.3 µm 3 in each nucleus (Bohrer et al, 2018).…”
Section: Immunofluorescence and Cell Counting Analysesmentioning
confidence: 99%
“…The developmental competence of embryos, including mice (Wang et al, 2013), humans (Kort et al, 2016), and pigs (Bohrer et al, 2015(Bohrer et al, , 2018Dicks et al, 2017), is affected by DNA damage. Moreover, treatment with epigenetic modulators, such as histone deacetylates inhibitors, during embryo culture promoted DNA repair and improved embryo development (Bohrer et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Disrupted TUDCA/TGR5 signaling has a significant impact on the GDR. During early embryo development, it has been shown that embryos primarily utilize the HR pathway in response to DSBs caused by UV radiation, with DsiRNA targeting ATM, but not DNAPK, significantly reducing the proportion of blastocysts that developed and their quality (Bohrer et al, ). Considering the superior fidelity and efficiency of the HR pathway (Blackford & Jackson, ; Khanna & Jackson, ), it is not surprising that embryos would preferentially employ this pathway in preventing replication of damaged DNA and the subsequent deleterious effects.…”
Section: Discussionmentioning
confidence: 99%
“…Considering there was no difference seen in cell number and, in fact, increased XIAP mRNA abundance to prevent cell death, these changes can be interpreted as a successful adaptation from the perspective of the embryo cell, or blastomere (Dicks et al, ) allowing survival despite being stressed and damaged. On the other hand, at the organismal level, the upregulation of NHEJ over HR in response to nuclear stress could represent a pathological adaptation (Dicks et al, ), raising concerns of impaired genome integrity and abnormal embryo development (Bohrer et al, ). Survival of these blastomeres carrying DNA damage will likely have deleterious consequences that will manifest during embryonic or subsequent life stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation